Working in the Midst of Trauma: Exposure and Coping in News Camera Operators. Issue 4 (19th May 2019) - Ikizer, Gözde; Karanci, A. Nuray; Kocaoglan, Sibel
Abstract: News camera operators are among the first responders to crises, emergencies, and other human suffering. This study is an attempt in the literature to explore trauma exposure and coping in news camera operators who are likely to experience primary and secondary traumatization simultaneously. Qualitative data from 20 news camera operators were analyzed using interpretative phenomenological analysis. Two superordinate themes emerged: (a) physical and psychological impact and (b) strategies of coping. The results highlight challenges associated with the work of news camera operators. Mental health support and training for this group of media professionals are strongly recommended at the undergraduate and/or organizational levels.